Determinants of survival of newly created SMEs in the Brazilian manufacturing: An econometric study - Luis Otávio Façanha; Marcelo Resende; Vicente Cardoso (Center for Economic Studies and ifo Institute (CESifo), 2012)
The paper investigates the survival of newly created small and medium enterprises in Brazilian manufacturing taking as reference the 1996-2005 period. The econometric analysis relies on time-varying version of the proportional hazard rate model that controls for unobserved heterogeneity. The evidence mostly corroborates previous findings for developed countries. Salient results include the positive role played by firm size, industry size and industry growth on survival and yet the negative influence exerted by industrial concentration and entry rate.
Keywords: L25; M21; 330; survival; small and medium enterprises; manufacturing industry; Unternehmensgründung; Klein- und Mittelunternehmen; Mittelständische Industrie; Unternehmensentwicklung; Schätzung; Brasilien